THE CONCEPTUAL FRAMEWORK FOR THE RESOURCES MANAGEMENT ATTRIBUTES AND AIRCRAFT MAINTENANCE EFFICIENCY IN THE AVIATION INDUSTRIES IN OMAN - Rawahi, Said Hamed Al; Jamaluddin, Zaharuzaman Bin; Bhuiyan, Abul Bashar (International Journal of Accounting & Finance Review, 2020)
The main purpose of the study is to investigate existing available literature for determining of relevant factors that have cause and effects on the ensuring of aircraft maintenance efficiency in the aviation industry in Oman. Therefore, the study uses available sources of existing literature based on the four main keywords ‘aircraft maintenance efficiency’, ‘aircraft maintenance and resource management attributes ‘or ‘effective planning and aircraft maintenance, and ‘internal control and aircraft maintenance, etc., and explored to covers from Google Scholar, ProQuest, and Scopus, and other online resources. The study also justified of above summary literature gap by the most relevant theories such as stakeholder, agency, and resource-based theories accordingly. Based on this extensive review, the study developed a conceptual framework, where effective planning and internal control have moderating role on the relationship between the resource management attributes and aircraft maintenance efficiency in the aviation industry in the sultanate of Oman. The summary review findings of the study will fill the gap in the existing body knowledge especially prime factors affecting the attainment of aircraft maintenance efficiency, resource management attributes, effective planning and ‘internal control and aircraft maintenance in the aviation industry in the sultanate of Oman. The study recommends to justify this conceptual framework by empirical data from the in the aviation industry in the sultanate of Oman and draw a policy guideline for ensuring of determining of relevant factors that have cause and effects on the ensuring of aircraft maintenance efficiency in the aviation industry in Oman.